2019
DOI: 10.1002/bse.2427
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sustainability (environmental, social, and governance) disclosure and board diversity on firm value: The moderating role of industry sensitivity

Abstract: Using a large panel data set comprising 812 listed European firms, this study investigates whether sustainability disclosure (environmental, social, and governance) and female representation on boards affect firm value. We observe a positive impact of sustainability disclosure and board gender diversity on firm value, suggesting that the best management practices, enhanced stakeholder trust, and female representation on boards improve firm value. We observe that the firms in sensitive industries achieve superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
161
7
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(250 citation statements)
references
References 38 publications
19
161
7
3
Order By: Relevance
“…To test the moderating role of industry in H4, we add the interaction between the interlocks measure and a dummy variable indicating if firms belong to the more environmentally impacting industries ( More Environmentally Impacting ) to our model. Moderation is widely used in environmental studies, such as Cordeiro et al (2020); Qureshi et al (2020); Rajesh and Rajendran (2020); Ren, He, Zhang, and Chen (2019); Wijethilake and Upadhaya (2020). Thus, our model becomes the following: italicGHG0.25emEmissons Intensityit=β0+β1Interlock Measureit+β2More Environmentally Impactingi++β3Interlock Measureit*More Environmentally Impactingi+β4italicControls+k=19λkitalicYear+μit, where the interlock measure is one of the four measures: (a) Total Interlocks , (b) Same Industry Interlocks , (c) Cross Industry Interlocks , and (d) Interlocks with Leaders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the moderating role of industry in H4, we add the interaction between the interlocks measure and a dummy variable indicating if firms belong to the more environmentally impacting industries ( More Environmentally Impacting ) to our model. Moderation is widely used in environmental studies, such as Cordeiro et al (2020); Qureshi et al (2020); Rajesh and Rajendran (2020); Ren, He, Zhang, and Chen (2019); Wijethilake and Upadhaya (2020). Thus, our model becomes the following: italicGHG0.25emEmissons Intensityit=β0+β1Interlock Measureit+β2More Environmentally Impactingi++β3Interlock Measureit*More Environmentally Impactingi+β4italicControls+k=19λkitalicYear+μit, where the interlock measure is one of the four measures: (a) Total Interlocks , (b) Same Industry Interlocks , (c) Cross Industry Interlocks , and (d) Interlocks with Leaders.…”
Section: Methodsmentioning
confidence: 99%
“…Lu and Herremans (2019) expanded on Li et al (2017) by investigating actual performance and gender diversity, also finding an industry moderating effect. Regarding sustainability disclosure and board diversity as it relates to firm value, Qureshi, Kirkerud, Theresa, and Ahsan (2020) found that the industry was an important moderating variable in their research. More environmentally impacting industries (e.g., resource extractive and manufacturing) feel greater pressure from their stakeholders to reduce emissions compared with less environmentally impacting industries (e.g., retail and service) (Bansal & Clelland, 2004; Hart, 1995; Herremans, Herschovis, & Bertels, 2009).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Corporate governance is also a factor that may have an effect on the market value (Caixe & Krauter, 2014;Li et al, 2015;Santos et al, 2019), so a dummy was used to capture the entities listed in the new market and a dummy for when the statements were audited by a Big Four audit company. There are theoretical aspects in the literature that indicate that the adoption of sustainable practices has an effect on the firm value, one that predicts that the market tends to recognize sustainable companies and consequently value them, and another that deals with the market that does not recognize since these expenses reflect only expenses to shareholders (Qureshi et al, 2020;Yu & Zhao, 2015), to capture this aspect, a dummy for companies listed on the ISE was included. Characteristics of organizations can also affect the market value of the entity, including the age of the organization, ownership control, and family business (Brown et al, 2019;Goes et al, 2017;Jara et al, 2019;Klein et al, 2005;Rossi & Harjoto, 2019) were the characteristics controlled in this study.…”
Section: Controlmentioning
confidence: 99%
“…Currently, sustainability is getting prestigious and organizations are making it a piece of their standard measures to get longer range benefits. The tripled main concern (TBL) viewpoint including environmental, social and financial impacts, empowers us to reevaluate our procedures to work with and accomplish more (Martens et al 2017;Qureshi et al, 2020). This study reconfigures the significance of essential factors enhancing sustainability in construction sector project and how its incorporation helps in project success through moderating role of project manager's management expertise.…”
Section: Introductionmentioning
confidence: 95%